Yerba Mate: The Natural Boost Your Body Craves - Malwina Draim; Aneta Rostkowska; Sebastian Kupisiak; Natalia Pasierb; Barbara Rękas; Michalina Kosowska; Wiktoria Dzierzgowska; Julia Latocha (Quality in Sport, 2025)
Introduction: Yerba Mate (Ilex paraguariensis) is a traditional South American infusion known for its stimulant and antioxidant properties. Historically consumed for its energizing effects, it was also regarded as a medicinal remedy by indigenous cultures, used to treat fatigue, stress and digestive issues [1, 2]. In recent decades, Yerba Mate has gained global recognition and has garnered scientific interest due to its potential health benefits such as improving cardiovascular health, metabolic function and supporting physical performance [1–5]. Its rich content of polyphenols, xanthines and saponins may contribute to a range of protective and restorative effects on the human body [1, 8].